(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
The histological analysis of both the local and Sherazi cat was conducted to comprehend their distinct differences. These felines, classified under the scientific name (Felis catus), are members of the Felidae family . Thirty tongue samples were gathered from cats that frequented veterinary clinics, with each type of cat comprising fifteen samples. The results of our histological study of the parts of tongue in the local and adult Sherazi cat showed that it consists of three main layers: the mucosal layer, submucosa layer, and muscular layer in all its regions. The mucosal layer in the dorsal surface of the tongue is composed of keratinized stratified squamous epithelium, the tunica submucosa consisted of loose Connective tissue containing lingual glands in root region only, which are of two types: mucous and serous glands. The tunica muscularis appears as a bundles of muscle fibers in three directions, longitudinal, transverse and perpendicular. The study also found the presence of four types of lingual papillae on the dorsal surface of the tongue (filiform, fungiform, foliate, and circumvallate papillae).